2013
DOI: 10.1002/bit.24833
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lignin‐degrading bacteria from rainforest soils

Abstract: The deconstruction of lignin to enhance the release of fermentable sugars from plant cell walls presents a challenge for biofuels production from lignocellulosic biomass. The discovery of novel lignin-degrading enzymes from bacteria could provide advantages over fungal enzymes in terms of their production and relative ease of protein engineering. In this study, 140 bacterial strains isolated from soils of a biodiversity-rich rainforest in Peru were screened based on their oxidative activity on ABTS, a laccase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 100 publications
(90 reference statements)
3
124
1
1
Order By: Relevance
“…ISTKB was higher than the earlier reported activity for bacterial consortia (Chandra and Singh 2012). Although, intracellular laccase production in bacteria has been reported earlier (Huang et al 2013), the production of intracellular laccase in Pandoraea sp. is being reported for the first time in this study.…”
Section: Oxidative Ligninolytic Enzyme Assaycontrasting
confidence: 51%
“…ISTKB was higher than the earlier reported activity for bacterial consortia (Chandra and Singh 2012). Although, intracellular laccase production in bacteria has been reported earlier (Huang et al 2013), the production of intracellular laccase in Pandoraea sp. is being reported for the first time in this study.…”
Section: Oxidative Ligninolytic Enzyme Assaycontrasting
confidence: 51%
“…For one, the products of SCF1 anaerobic lignin reduction remain unclear. These products could include phenolic aldehyde, acid, or ketone monomers that are observed to be released during alkaline CuO oxidation (Thevenot et al, 2010), or any of the catabolic pathway intermediates that have observed during anaerobic lignin degradation of other bacteria, such as the catabolic pathways described for degradation of lignin and lignin-derived compounds in S. paucimobilis SYK-6 (Masai et al, 2007) and others (Harwood and Parales, 1996; DeRito et al, 2005; McLeod et al, 2006; Bugg et al, 2011b; Huang et al, 2013). The use of lignin dimers or model lignin compounds such as artificial or naturally occurring aromatics would permit measurement of specific rates of degradation of specific bonds present in lignin (Kato et al, 1998; Koga et al, 1999; Chang, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Known potential lignin-degrading bacteria are in the groups α-proteobacteria, γ-proteobacteria, Firmicutes and Actinomycetes (Bugg et al, 2011b) and most bacteria employ extracellular peroxidases, which require oxygen availability (Bugg et al, 2011a). For example, the novel isolates in the phylum Firmicutes Bacillus pumilus strain C6 and Bacillus atrophaeus strain B7 were identified to have very high laccase activity as well as the ability to aerobically degrade Kraft lignin and the lignin model dimer guaiacylglycerol-b-guaiacyl ether (Huang et al, 2013). Many bacterial processes have been successfully engineered into consolidated bioprocessing for biofuels, such as cellulose conversion to sugars (saccharification) and ionic liquid pretreatment tolerance (Blanch et al, 2008; Lee et al, 2008; Singh et al, 2009), with an emerging role for bacterial lignin degradation (Bugg et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…B-9, which was isolated from eroded bamboo slips, was found able to degrade kraft lignin to low molecular weight compounds and use these as the sole source of carbon (Chen et al 2012). In another study, 140 bacterial strains were isolated from soil of a rainforest rich in biodiversity, and Bacillus pumilus as well as Bacillus atrophaeus were shown capable of degrading kraft lignin and lignin model dimers (Huang et al 2013). Amycolatopsis sp., Pseudomonas putida strains, Acinetobacter ADP1, and Rhodococcus jostii were found able to depolymerize high molecular weight lignins and also catabolize a wide variety of low molecular weight lignin aromatics (Salvachúa et al 2015).…”
Section: Introductionmentioning
confidence: 99%